Lignocellulosic biomass fractionation with the use of deep natural eutectic solvents (Research, Society and Development, 2022)
Brazil has a privileged position as a leader in the integral use of vegetable biomass because it has the largest biodiversity on the planet. Adding value to a refinery is associated with the treatment and disaggregation of the biomass components. There are processes applied to biomass fractionation to remove or break the layers of lignin and hemicellulose, which allows enzymes to access cellulose more easily. In view of this a great diversity of technological routes can be used, and alternative techniques that have been developed such as the use of the natural deep eutectic solvent (NADES). Thus, the objective of the present work was to perform the fractionation of the bark biomass from E. urograndis species into two fractions: cellulose rich fraction (CRF) and lignin rich fraction (LRF) using NADES. In this process three conditions were applied for biomass fractionation: conventional heating at 100ºC, microwave radiation with power of 600W and 1000 W, and room temperature at 25ºC. The percentages obtained through conventional heating were 72,25% of CRF, 27,75% of LRF; 72,54% of CRF with microwave radiation at a power of 1000W, 27,46% of LRF. The techniques used for characterization of CRF were: Fourier transformed infrared (FTIR) spectroscopy and X-ray diffractometry (XRD) for crystallinity analysis and scanning electron microscopy (SEM). For characterization of LRF the techniques were used: UV-vis and FTIR spectroscopy. The use of NADES a low cost, sustainable organic solvent combined with microwave radiation proved to be efficient for biomass fractionation.